vv
vv

:

Internet Explorer 6 - v

Powered by Asuult.Net

(, ) . , (, ) . vv .

- , f(x)f(y) f (..) .

f(x)=2 .. . (-1)2=(1)2 . .. . 2 뺺 .. : f(x) = { [0, ) x2 }. .. vv v :

.. . ( .) .. . ( vv v .)

(b, a) f vvv (a, b) f -1 . f -1 f - .

17

Ǻ f .. f -1 .

f -1 - . f(b)=f(c) f - (b, f(b)), (c, f(c)) . (c, f(c))=(b, f(c)) (f(b), b), (f(c), c) f -1 - . f -1 - v b=c . b=c f - .. .

f -1 f g(x)=x vv ( ).

f -1 - vv f . (f -1)-1=f . . .. .

(a, b) f - , (b, a) f -1 - . b = f(a), = f -1(b) . f -1(x) = y f(y) = x .

f(f -1(x))=x . (f -1 - )
f -1(f(x))=x . (f - )

, y=f(x) x, y "". - . , y=(x-1)3 =(-1)3 .
-1=1/3, =1/3+1 . 人 v v:

18

f .. v f , . (, , .)

19

f .. v f -1 v.

v ( ): 18- () "" . 19- , f 13- . f [a, b] () [f(a), f(b)] - " " v. f -1 [f(a), f(b)] . [a, b]. " " v ( vv v.) , .

f -1 v : !

20

f .. v, f -1(b)
(f -1(b)) 0 f -1 b
.

(f -1()) = . 8-

(1) (f -1(b)) (f -1)'(b) = 1

. v, (f -1(b)) 0 . f -1 .. (f -1)' 0 . (1) .

, (f -1(b)) = 0 f -1 b v . v (1) - v. :)

, vv v . v v vv! ( .)

<-- | vv | -->


?

:
e-mail:
v:
 


vv | vv | | | | | Links |

Copyright © 2003 . . .